Lactate in the Regulation of Tumor Microenvironment and Therapeutic Approaches - de la Cruz-López, Karen G.; Castro-Muñoz, Leonardo Josué; Reyes-Hernández, Diego O.; García-Carrancá, Alejandro; Manzo-Merino, Joaquín (Frontiers in Oncology, 2019)
Tumor cells must generate sufficient ATP and biosynthetic precursors in order to maintain cell proliferation requirements. Otto Warburg showed that tumor cells uptake high amounts of glucose producing large volumes of lactate even in the presence of oxygen, this process is known as “Warburg effect or aerobic glycolysis”. As a consequence of such amounts of lactate there is an acidification of the extracellular pH in tumor microenvironment, ranging between 6.0-6.5. This acidosis favors processes such as metastasis, angiogenesis and more importantly, immunosuppression, which has been associated to a worse clinical prognosis. Thus, lactate should be thought as an important oncometabolite in the metabolic reprogramming of cancer. In this review, we summarized the role of lactate in regulating metabolic microenvironment of cancer and discuss its relevance in the up-regulation of the enzymes lactate dehydrogenase (LDH) and monocarboxilate transporters (MCTs) in tumors. The goal of this review is to expose that lactate is not only a secondary product of cellular metabolic waste of tumor cells, but also a key molecule involved in carcinogenesis as well as in tumor immune evasion. Finally, the possible targeting of lactate production in cancer treatment is discussed.